Urinary and fecal incontinence, pelvic floor disorders, sexual dysfunction and overweight, obesity and metabolic syndrome - Krotkiewski, Marcin; Stangel-Wójcikiewicz, Klaudia; Mika, Marcin; Jach, Robert (Menopause Review/Przegląd Menopauzalny, 2012)
Urinary incontinence, fecal incontinence, sexual dysfunction and erectile dysfunction show higher prevalence in overweight and obese people. Urinary incontinence is more common in women with abdominal obesity (visceral obesity) and is associated with elevated abdominal pressure that causes secondary pressure in bladder. Sexual dysfunctions are more common in women due to their excessive weight. They might experience urinary and/or fecal incontinence, impairment of sphincter muscles and drop of pelvic organs. The urinary incontinence in women and erectile dysfunction in men show a clear correlation with the presence of indices of the metabolic syndrome [hyperlipidemia, hyperglycemia, elevated CRP (C-reactive protein), TNF-α (tumor necrosis factor), IL-6 (interleukin), IL-8 (chemokine), hypertension and atherosclerotic changes in blood vessels]. The occurrence of erectile dysfunction in men is closely associated and proportional to the severity of the metabolic syndrome. Decreased production of nitric oxide (NO) with the consecutive impairment of vasodilatation is a causal factor contributing to this disorder. The use of dietary treatment, increased physical activity, and in morbid obese persons over 30 years of age, surgical treatment is contributing to remarkable symptomatological improvement. Because of poor self reporting, medical staff should pay more attention to sexual dysfunction, fecal and urine incontinence in women and erectile dysfunction in men (which are not spontaneously reported) and their association with overweight and the metabolic syndrome. There is also a need for follow-up on potential improvements and effectiveness of therapy which should obligatorily include the reduction of body weight.